Physical modelling and computer simulation of the cardiorespiratory system based on the use of a combined electrical analogy. Issue 1 (2nd January 2021) - Fernandez de Canete, J.; Cuesta, D.; Luque, A.; Barbancho, J.
ABSTRACT: Modelling the human cardiorespiratory system using computer simulation tools can serve to help physicians to comprehend the causes and development of cardiorespiratory diseases. The objective of this paper is to develop an integrated model of the cardiovascular and respiratory systems, along with their intrinsic control mechanisms, by combining analogous hydraulic-electric and diffusion-electric circuits, respectively. This modelling task is performed in object-oriented language in SIMSCAPE using the physical interconnected components to define the underlying dynamic equations. Simulation steady state results under rest and under variable physical exercise conditions, as well as under limiting conditions show a high qualitative agreement with clinical observations reported in literature. This object-oriented modelling approach, based on the combined use of electrical analogies, proves to be avaluable tool as a test bench for different strategies aimed to qualitative prediction of the effects of cardiorespiratory interactions during exercise, thus avoiding the formulation of complex mathematical models.